Political Culture and Discrimination in Contests - Gil S. Epstein; Yosef Mealem; Shmuel Nitzan (Center for Economic Studies and ifo Institute (CESifo), 2010)
Many economic and political decisions are the outcome of strategic contests for a given prize. The nature of such contests can be determined by a designer who is driven by political considerations with a specific political culture. The main objective of this study is to analyze the effect of political culture and of valuation asymmetry on discrimination between the contestants. The weights assigned to the public well being and the contestants' efforts represent the political culture while discrimination is an endogenous variable that characterizes the mechanism allocating the prize. We consider situations under which the optimal bias of the designer is in favor of the contestant with the larger or smaller prize valuation and examine the effect of changes in the political culture and in valuation asymmetry on the designer's preferred discrimination between the contestants. Focusing on the two most widely studied types of contest success functions (deterministic all-pay-auctions and logit CSFs), we show that an all-pay auction is always the preferred CSF from the point of view of the contest designer. This result provides a new political-economic micro foundation to some of the most commonly used models in the contest literature.
Keywords: 330; rent seeking; political culture; discrimination; contests; logit contest success function; All-Pay-Auction; Wettbewerb; Extensives Spiel; Auktionstheorie; Mechanism Design; Politische Kultur; Rent Seeking; Diskriminierung; Theorie